How Do The Community Health Nurses’ Experience in The Strategies of Non-Communicable Disease (NCD) Promotion and Prevention? - Rizkiyani Istifada; Etty Rekawati; Wiwin Wiarsih (Poltekkes Kemenkes Jakarta III, 2021)
Nurses have an important task in the strategy of intervention to reduce of Non-Communicable Diseases (NCD)’ incidence. Community health nurses have tried to control the problem of NCD. However, the incidence of NCD has not decreased as expected. The promotion and prevention of non-communicable diseases are one of the efforts to control PTM. This study aims to explore the experience of nurses in implementing the strategies of NCD’ promotive and preventive. This study used a qualitative descriptive phenomenological design. A total of 16 community health nurses were selected using purposive sampling. The inclusion criteria of this study were (1) nurses who served at the community health center for a minimum of 6 months, (2) performed individual health services in the community health center and carried out family visits and services in the community. The data were analyzed using Colaizzi's approach. This research was approved by the Committee of Ethics in the Faculty of Nursing, Universitas Indonesia. This study resulted in five strategies of nurses implementing to NCD’ promotion and prevention, include (1) health education, (2) partnership with community health workers, (3) coordination, (4) stand with the community, (5) monitoring the change of behavior in the community. Nurses’ experience of NCD’s promotion and prevention in the community health center still needs improvement to achieve holistic and comprehensive health services. Nurses should be attention to the preparation of themselves before implementing the promotion and prevention, such as preparation of the topic, communication with colleagues and communities, and doing a partnership with multisectoral.